Risk factors for central venous catheter-related bloodstream infection in oncology patients: an integrative review - Bastos, Elaine Cristina Bezerra; Carvalho, Francisco Samuel; Chaves, Filipe Nobre; Costa, Fábio Wildson Gurgel; Costa, Antonio Neudimar Bastos; Mesquita, Camila Melo; Carvalho, Maria Raquel Raquel R (Brazilian Journal of Oncology, 2022)
The aim of this integrative review was to identify scientific studies on risk factors for bloodstream infections associated with central venous catheters (CVC) in cancer patients. The research question was formulated according to the PICO framework. An electronic search was conducted on the SciELO digital library, the Virtual Health Library, and the MEDLINE/PubMed databases using the descriptors “cancer”, “infection”, “central venous catheters”, and “risk factors”. A total of 356 publications were identified (356 in PubMed, 00 in the VHL, and 00 in SciELO). Based on the PRISMA guidelines, 32 articles were included in this review. Recent study dates from 2021. The handling of the central catheters by professionals and the administration of parenteral nutrition were the main risk factors for CVC infections. The implementation of basic healthcare and hygiene measures is essential for the prevention and reduction of bloodstream infections associated with central catheters.
Keywords: Central venous catheters; Cross infection; Risk factors